FEATURES OF THE DISTRIBUTION OF ALTITUDINAL-BELT VEGETATION OF THE UZYNKARA (KETPEN) RIDGE (Experimental biology, 2025)
The article shows the results of the Uzynkara (Ketpen) range vegetation studies during route and semi-stationary studies. The article presents the analysis of the Uzynkara ridge vegetation on specific profiles and summarizes all available data on the patterns of altitudinal zonality of vegetation. The flora of the territory we studied is comparatively rich and includes 1890 species of higher vascular plants belonging to 120 families and 596 genera. About 67.8% of the entire flora are perennial herbaceous hemicryptophytes. A very large proportion (more than 21%) are summer-green biennials (annuals and biennials) - therophytes, i.e. plants with an accelerated development cycle. This feature - the abundance of annuals and biennials and the presence of a large number of ephemerals and ephemeroids - is characteristic of the mountain flora of the entire Middle Asia. In this territory, we have identified the following altitudinal zonality zones, each with its own specific type ...
Keywords: Groups of plant communities, altitudinal zones, Uzynkara - Ketpen